GAMBARAN PELAKSANAAN TERAPI PADA WANITA PENDERITA KANKER PAYUDARA DI RSUD BANYUMAS TAHUN 2013 - Reni Dwi Setyaningsih (Universitas Harapan Bangsa Purwokerto, 2015)
Background: Breast cancer is the cancer with the highest incidence rate of thenumber 2 after cervical cancer. The number of breast cancer patients around theworld continues to increase. The direct causes of breast cancer up to nowunknown, regarding treatment, among experts in the world are also manydifferences of opinion. There are many treatment of breast cancer include,Lumpectomy, Mastectomy, chemotherapy, radiation and hormonal therapy.Objective: To determine the description of the implementation of the therapy inwomen with breast cancer in Banyumas General Hospital in 2013. Methods: This research is quantitative descriptive retrospective study approach.The sample used is total sampling, samples of this study were all women withbreast cancer who carry out road maintenance in hospitals Banyumas ie 40patients. Results: From the results, the majority of respondents were age â‰¥ 50 years a totalof 33 respondents (82.5%), mostly there is no family history of breast cancer in asmany as 27 respondents (67.5%), the majority of respondents have as much paritymultiparas 25 respondents (62.5%), the majority of breast cancer treatment ischemotherapy as much as 15 respondents (37.5%).Conclusion: The majority of breast cancer treatment is with chemotherapyKeywords: Breast Cancer Treatment, Age, Family History, Parity